The Occurrence of Klebsiella pneumoniae in Drainage Fluid After Pancreaticoduodenectomy: Risk Factors and Clinical Impacts - Yang, Yifei; Fu, Xu; Cai, Zhenghua; Qiu, Yudong; Mao, Liang (Frontiers in Microbiology, 2021)
To investigate the risk factors and clinical impacts of the occurrence of Klebsiella pneumoniae (K. pneumoniae) isolated from drainage fluid in patients undergoing pancreaticoduodenectomy (PD). Clinicopathological data of all patients who underwent PD from January 2018 to March 2021 were analyzed retrospectively. The univariate and multivariate analysis were performed to identify independent risk factors for the occurrence of K. pneumoniae in drainage fluid and its clinical impacts on postoperative complications. Of the included 284 patients, 49 (17.2%) patients isolated K. pneumoniae in drain samples after PD. Preoperative biliary drainage (OR=1.962, P=0.037) independently predicted the contamination of K. pneumoniae in drain samples after PD. The rate of clinically relevant postoperative pancreatic fistula (CR-POPF), major complications (Clavien–Dindo Grade≥Ⅲ), post-pancreatectomy hemorrhage (PPH), organ/space surgical site infection (SSI) and biliary leakage (BL) were significantly higher in K. pneumoniae positive group both in the univariate and multivariate analysis. Preventive measures and treatments for combating K. pneumoniae contamination may be beneficial to the perioperative outcomes of patients after PD.